1998
DOI: 10.1007/s004210050357
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and blood pressure responses to isometric exercise in young and older men

Abstract: The aim of this study was to examine the isometric endurance response and the heart rate and blood pressure responses to isometric exercise in two muscle groups in ten young (age 23-29 years) and seven older (age 54-59 years) physically active men with similar estimated forearm and thigh muscle masses. Isometric contractions were held until fatigue using the finger flexor muscles (handgrip) and with the quadriceps muscle (one-legged knee extension) at 20%, 40%, and 60% of the maximal voluntary contraction (MVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 19 publications
5
65
0
10
Order By: Relevance
“…Such a static exercise is essentially the same as "rhythmic isometric exercise" (Asmussen, 1981). During static, one-legged knee extension at 20%, 40%, and 60% MVC, continuously increasing HR and BP were observed, where the exercise duration at 20% MVC was the longest (4.6 min on average) (Smolander et al, 1998 unilaterally or bilaterally for 3 or 6 minutes, comparing the difference between the cases in both a dynamic and a static mode with two different intensities, 20% MVC and 40% MVC.…”
Section: Introductionmentioning
confidence: 96%
“…Such a static exercise is essentially the same as "rhythmic isometric exercise" (Asmussen, 1981). During static, one-legged knee extension at 20%, 40%, and 60% MVC, continuously increasing HR and BP were observed, where the exercise duration at 20% MVC was the longest (4.6 min on average) (Smolander et al, 1998 unilaterally or bilaterally for 3 or 6 minutes, comparing the difference between the cases in both a dynamic and a static mode with two different intensities, 20% MVC and 40% MVC.…”
Section: Introductionmentioning
confidence: 96%
“…Understanding the pressor response during dynamic resistance exercise using large muscle groups is essential for exercise prescription. However, most previous studies have focused on static resistance exercise (11,12,16,33), and have provided little information regarding the cardiovascular response during dynamic resistance exercise (10), or the interaction between age and BP response to dynamic resistance exercise using large muscle groups. We found that pressor responses during dynamic resistance exercise at relative intensities were lower in middle-aged than in young men, suggesting that the BP response to dynamic resistance exercise may be attenuated with advancing age despite age-associated arterial stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic and diastolic blood pressures (BPs) rise rapidly to extremely high values during heavy weight-lifting exercise (10), and BPs are extreme even when exercise is performed with a relatively small muscle mass (11,12). Most previous studies have focused on the BP responses to resistance exercise in young adults (13)(14)(15), and thus have provided little information regarding BP responses in middle-aged and older individuals (12,16). Furthermore, the interaction between age and BP response for dynamic resistance exercise using large muscle groups has not been reported in middle-aged men with stiffening arteries or young men with compliant arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Respostas mais exuberantes, não observadas no presente estudo, quer da FC, quer da PA ao exercício físico, podem, juntamente com as patologias cardiovasculares características deste escalão etário, aumentar significativamente o "stress" cardiovascular e, consequentemente, aumentar o factor de risco associado à exercitação (26,30) . A utilização simultânea dos membros superiores e inferiores durante os períodos do aquecimento e da resistência aeróbia poderão justificar os maiores valores de FC e PA, uma vez que a sobrecarga fisiológica é maior no exercício realizado com as extremidades superiores em comparação com aquele empreendido pelas extremidades inferiores (35) .…”
Section: Rp Aqunclassified